TINJAUAN HUKUM TERHADAP ATURAN INTERNASIONAL MENGENAI LIBERALISASI PERDAGANGAN JASA MELALUI KERANGKA PERJANJIAN WTO DAN KERANGKA PERJANJIAN ASEAN - Sumanggam Wahyu; Mahmul Siregar; Jelly Leviza (Journal of USU International Law, 2014)
ABCTRACT Free trade interaction one state with another, should have any regulation of law international. Obviously, to arrange trade regulation with another states, and obligate any law regulation to captivate, if appear any dispute on that trade transaction According from that idea, issues that appointed on this observation are law international regulation about liberation trade in service, regulation dispute settlement on WTO frame agreement and ASEAN frame agreement, position of regulation AFAS directed regulation on GATS as frame agreement WTO. This observation using yuridis normative approach which to learn assembling law international principles about liberation trade on service. From the result of the observation, that law international regulation about liberation trade in service on frame agreement WTO is General Agreement Trade in Service (GATS)  which the rule of basic to enclose on Annex 1b GATS. Whereas on frame agreement ASEAN, through implementation AFAS (ASEAN Framework Agreement on Service) within elimination trade border on services with on member of ASEAN. Dispute settlement on frame agreement WTO through Special Body , there is Dispute Settlement Body, whereas on ASEAN, through High Council which formed by Senior Economic Officials Meeting (SEOM) and the rule of law suitable with Treaty of Amity and Cooperation in South-East Asia (TAC). Position of regulation AFAS directed rule onward GATS , there is the implementation economic regionalism which the principle according WTO agreement. Keyword : Liberation Trade in Service, GATS, AFAS